Randomized control trial of adenoma detection rate in Endocuff‐assisted colonoscopy versus transparent hood‐assisted colonoscopy. Issue 9 (21st July 2019) - Imaeda, Hiroyuki; Yamaoka, Minoru; Ohgo, Hideki; Soma, Hiromitsu; Ashitani, Keigo; Miyaguchi, Kazuya; Tsuzuki, Yoshikazu; Hosoe, Naoki; Nakamoto, Hidetomo
Abstract: Background and Aim: Transparent hood‐assisted colonoscopy (TAC) has been reported to improve the cecal insertion rate and adenoma detection rate (ADR). An endoscopic cap (Endocuff) with two rows of soft wings was recently developed to improve ADR, by flattening the mucosal folds during withdrawal. This randomized prospective control study aimed to compare ADR between Endocuff‐assisted colonoscopy (EAC) and TAC. Methods: A total of 513 patients undergoing colon adenoma screening were included. EAC was performed in 256 patients and TAC in 260 patients. Cecal intubation rate, cecal intubation time, ADR, and mean adenoma number per patient (MAP) were investigated in both groups (clinical trial registration: UMIN000016278). Results: We excluded six patients in the EAC group and two patients in the TAC group because of colonic stenosis due to colonic adenocarcinomas. Finally, 250 patients (151 men/99 women, median age 62.1 years) were assigned to EAC and 258 patients (165 men/93 women, median age 64.3 years) were assigned to TAC. There were no significant differences in cecal intubation rate, intubation time, withdrawal time, and cleanliness score between groups. The ADR was 50.8% in EAC and 52.7% in TAC, with no significant difference ( P  = 0.666). The MAP was 1.35 in EAC and 1.20 in TAC, with no significant difference ( P  = 0.126). However, The MAP of diminutive adenomas (< 5 mm) tended to be higher in EAC than in TAC ( P  = 0.077). There was no significant difference in MAP in each segment between groups. Conclusions: Endocuff‐assisted colonoscopy might be equivalent to TAC in cecal intubation time, ADR, and MAP.